Bionic design and 3D printing of porous titanium alloy scaffolds for bone tissue repair. (1st April 2019) - Zhao, Li; Pei, Xuan; Jiang, Lihua; Hu, Cheng; Sun, Jianxun; Xing, Fei; Zhou, Changchun; Fan, Yujiang; Zhang, Xingdong
Abstract: Bone defect and osteoporosis are common in clinic which are seriously harmful for public health. Bionic bone tissue engineering scaffolds are very important for bone tissue repair and reconstruction. In this study, different bionic bone tissue engineering scaffolds were constructed by computer-aided design and fabricated by selected laser melting. Novel porous structures were designed by using parameterization modeling. The accurate models with key characteristics such as porosity and the mechanical property of scaffolds were studied. Compared with the designed model, the error of the selective laser melting (SLM) printed scaffold porosity was less than 2.73%. The mechanical properties of the prepared scaffold can be calculated by finite element analysis of 3D models, and the mechanical properties of the 3D printed samples were consistent with the model design. Through the design, manufacture, characterization and evaluation of the scaffold porous structures, the parametric modeling of porous titanium bone tissue engineering scaffold with good mechanical and biological properties was realized. Optimized design and precisely manufactured implants are very important for bone tissue repair and reconstruction.